THE IMPORTANCE OF CO2 LASER IN DERMATOLOGY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article explores the critical role of CO2 lasers in dermatology, examining their mechanisms, applications, and clinical outcomes. A comprehensive literature analysis highlights the advancements in laser technology, while the discussion provides insights into their future potential in skin treatments.